Morfoanatomia, histoquímica e ultraestrutura floral de espécies de annonaceae do cerrado - Natalia Arias Galastri (2013)
Annonaceae, included in Magnoliales, is the largest family among basal Angiosperms and there is a lack of structural, histochemical and ultrastructural data regarding the flowers of these plants, especially for those from the Brazilian savanna. Thus, the general aim of this study was to carry out a structural, histochemical and ultrastructural investigation of the flowers of seven Annonaceae species, typical of the biome Cerrado (Annona coriacea, A.crassiflora, A. dioica, A. emarginata, Duguetia furfuracea, Guatteria australis and Xylopia aromatica). Usual processing techniques for light microscopy, transmission electron microscopy and scanning electron microscopy were employed. A large number of Annonaceae have nutritive tissues in the petals, which constitute adaptation to cantharophily. For the studied species (Chapter 1), the nutritive region has uniseriate epidermis, with varied cell types, and parenchymatous mesophyll, with phenolic and crystal idioblasts, cells with pectic substances in the periplasmic space and starch reserve. Such cells show dense cytoplasmic matrix rich in mitochondria, dicty osomes and plastids in which large starch grains are highlighted. For Xylopia, this study presents an unprecedented record of flower nectary (Chapter 2), describing the anatomy and the ultrastructure of these nectaries in the inner petals of X. aromatica. The nectary is formed by secretory epidermis and parenchymatous subglandular tissue, with vacuolated cells rich in starch. In Chapter 3, ontogeny of the anther and the pollen, a relevant structure for understanding phylogenetic relationships in Annonaceae, is presented. It must be emphasized that the tapetum varies from amoeboid to glandular and that there are septate anthers, with parenchymatous or tapetal septa, as well as aseptate anthers. Meiosis is also variable and may be successive or simultaneous and, after microgametogenesis, the pollen is released in tetrads or monads. Chapter 4 characterizes the ovules of all seven species as bitegmic, crassinucellate and perichalazal , varying from anatropous to anacampylotropous, single or multiple per carpel, respectively, in basal or parietal placentation. Both megasporogenesis and megagametogenesis characterize the development of Polygonumtype. Finally, Chapter 5 shows the evaluation of 218 structural traits of flowers of the studied Annonaceae, using comparative phylogenetic methods to infer about the potential use of these traits to understand the flower evolution in the family. A phenogram was constructed indicating that, among other aspects, A. emarginata is the most distinct species among Annona, which shows that the inclusion of Rollinia in Annona should be revised. In addition, the most informative flower traits come from the corolla, especially from the inner petals, closely related to the elaborated process of pollination of the family.